(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2024)
The objective of this work was to characterize the phenology and determine the harvest points of snap bean varieties related to degree-day accumulation. The experiments were conducted in the Teaching Garden of the Federal University of Ceará, evaluating five bean genotypes. A randomized block design with three and five replications was used for experiments 1 and 2, respectively. Each experimental unit consisted of a 9.6 m seedbed. In the first experiment, the spacing adopted was 0.1 x 0.4 m (24 plants per plot). For the second experiment, the spacing adopted was 0.1 x 0.3 m (32 plants per plot). Phenological characterization was carried out, estimating the thermal requirement and the pod growth curve. The evaluated genotypes presented thermal requirements ranging between 1,282 and 2,111°C per day. The Habichuela genotype presented shorter cycle length, lower degree-day accumulation and higher initial pod growth compared to the others. It is recommended to harvest Feijão Vagem do Panamá (FVP), Habichuela and De Metro between the 10th and 15th day after fruiting. For Pronto Alívio and Quiura Bejuco, the harvest should be conducted at the 20th day after fruiting.